Action Learning Coaching. (May 2014) - O'Neil, Judy; Marsick, Victoria J.
The Problem: Action learning (AL) continues to be an important learning and development approach within organizations. Many successful AL programs use AL coaches to help facilitate the program and the learning that can occur within such programs. How might AL coaching be similar to, or different from, other types of coaching, and how might AL coaching be most effectively practiced? The Solution: A review of the conceptual, theoretical, and empirical research on AL coaching will address these questions and will enable a comparison of AL coaching and other types of coaching. We draw upon the research to demonstrate effective practice and the learning that can result from AL interventions. The Stakeholders: AL is used globally for learning, development, and change, and therefore, many organizational leaders are interested in the effective practice of AL and AL coaching. These leaders, human resource development (HRD) professionals, executives, internal and external coaches will benefit from this article.